AN ANALYSIS OF ENGLISH COMPOUND WORDS IN AN ARTTICLE OF LIFE AND STYLE COLUMN - Humaira R Maulidia; Kusumah Cita Mustika (Ma'soem University, 2022)
In a text, the kinds of words are found in many different word-formations. Therefore, every language shows new words such as inflection, derivation, and compounding. However, those methods cannot be used generally when it comes to texts. It can be determined whether a word is a noun or a phrase by a number of factors. As a result, this research will provide precise information about how compounding is used in the text. The research objectives are (1) What kinds of compound words found in the life and style columns of the Jakarta Globe article? (2) How the English compound words described in the life and style columns of the Jakarta Globe article? Further, this research employs a qualitative approach as suggested by Creswell (2014). The data were taken from an article in one of English newspapers in Indonesia entitled